Functioning of hyperbaric oxygen therapy and its use in the treatment of diabetic foot: what nursing care? (Research, Society and Development, 2021)
Objective: understand the functioning of Hyperbaric Oxygen Therapy, its use in the treatment of diabetic foot and the necessary nursing care. Methodology: This is an integrative literature review, carried out in August 2021, in the Virtual Health Library (VHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library databases Online (SCIELO) and Google Scholar, articles written in Portuguese, published in the period between 2017 and 2021, were used. Results: A total of 120 articles were found, after methodological rigor through the inclusion and exclusion criteria, 14 articles were selected, 1 article in the VHL, 1 in Lilacs, 0 in Scielo and 12 in Google Scholar. The analysis of selected articles was descriptive and predisposed to the data extraction stage: database, authors/year of publication, journal/type of study, title and theme. Conclusion: Given the results found in the literature, it can be observed that Hyperbaric Oxygen Therapy is an important ally in the treatment of wounds, proving to be positive for the treatment of diabetic foot syndrome and to be successfully performed, it is essential that nursing professionals perform all the necessary care, in order to avoid complications inherent to the environment, during and after the sessions, contributing to obtain the best results.